Performance Of Swamps Rice Lines In Shallow And Medium Swamp - Sumardi Sumardi; Mohammad Chozin (University of Prof. Dr. Hazairin, SH, 2023)
The development of swamp rice is currently generally carried out in shallow lowland swamp ecosystems, while middle lowland swamps and deep lowland swamps have not been used optimally. The main limiting factor besides the depth of the inundation is the relatively low level of soil fertility in both ecosystems, this is related to the level of weathering. The aim of this study was to evaluate the agronomic performance and yield of swamp rice lines resulting from crosses between Bengkulu local swamp rice and national superior varieties in two typologies of lowland swamps, namely shallow lowland swamps and middle lowland swamps. The experiment was carried out using a complete randomized block design with three replications. The swamp rice lines evaluated were UBPR1, UBPR2, UBPR3, UBPR4, UBPR6, UBPR7, UBPR8, UBPR9, UBPR10, UBPR11, and Inpara 4 and 6 varieties, as a comparison. Growth and development as well as plant yields decreased compared to the shallow swamps, except that the flowering and harvesting ages were generally more early in the middle swamps. The decrease in yield occurred for all tested lines including the control varieties, which ranged from 25.24 -70.95%. The lowest yield reduction occurred in UBPR 9 and UBPR 7 lines, respectively 25.24% and 37.15%, while the highest yield reduction occurred in UBPR 11, namely 70.95%, and the control variety (Inpara 4 and 6) respectively 61.13% and 66.12%.